2009
DOI: 10.1016/j.neuron.2008.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Long-Lasting Synaptic Plasticity and Memory

Abstract: Long-lasting forms of synaptic plasticity and memory are dependent on new protein synthesis. Recent advances obtained from genetic, physiological, pharmacological, and biochemical studies provide strong evidence that translational control plays a key role in regulating long-term changes in neural circuits and thus long-term modifications in behavior. Translational control is important for regulating both general protein synthesis and synthesis of specific proteins in response to neuronal activity. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
803
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 841 publications
(822 citation statements)
references
References 227 publications
14
803
1
4
Order By: Relevance
“…However, in contrast with the results obtained following injection of BDNF in the dentate gyrus, the neurotrophin was without effect on eEF2 phosphorylation in synaptoneurosomes isolated from the same region, suggesting that the arresting of elongation may be limited to non-synaptic sites. At the synapse, BDNF induces the phosphorylation of eIF4E (see above), thereby increasing protein synthesis, whereas in non-synaptic regions translation activity may be 5 0 -cap-independent and mediated by IRES [internal ribosomal entry site (Costa-Mattioli et al, 2009)]. The regulation of eEF2 in neurons may be more complex and will require further investigation, since studies performed in cultured cerebrocortical neurons showed a decrease in the phosphorylation of this elongation factor following acute and chronic stimulation with BDNF, which favors the interaction with the ribosomes and protein synthesis (Inamura et al, 2005;Nairn and Palfrey, 1987;Ryazanov et al, 1988;Takei et al, 2009).…”
Section: Bdnf and Regulation Of Translation Machinerymentioning
confidence: 99%
“…However, in contrast with the results obtained following injection of BDNF in the dentate gyrus, the neurotrophin was without effect on eEF2 phosphorylation in synaptoneurosomes isolated from the same region, suggesting that the arresting of elongation may be limited to non-synaptic sites. At the synapse, BDNF induces the phosphorylation of eIF4E (see above), thereby increasing protein synthesis, whereas in non-synaptic regions translation activity may be 5 0 -cap-independent and mediated by IRES [internal ribosomal entry site (Costa-Mattioli et al, 2009)]. The regulation of eEF2 in neurons may be more complex and will require further investigation, since studies performed in cultured cerebrocortical neurons showed a decrease in the phosphorylation of this elongation factor following acute and chronic stimulation with BDNF, which favors the interaction with the ribosomes and protein synthesis (Inamura et al, 2005;Nairn and Palfrey, 1987;Ryazanov et al, 1988;Takei et al, 2009).…”
Section: Bdnf and Regulation Of Translation Machinerymentioning
confidence: 99%
“…10,[74][75][76] At the circuit level, explicit short-term memory is thought to result from the strengthening of pre-existing synaptic connections and the covalent modification of preexisting proteins. 77 Long-term memory requires the synthesis of new proteins and the growth of new synaptic connections 78,79 through processes that depend on specific signalling pathways involving protein kinase A, mitogenactivated protein kinase, and cyclic adenosine monophosphate response element binding protein-1 and -2. [80][81][82] These protein systems, together with others, induce morphological changes at synapses, such as an increase in synaptic size and spine density, that are thought to stabilize long-term memory.…”
Section: General Anesthetics and The Neural Substrates Of Memorymentioning
confidence: 99%
“…TSC complex, Rheb and mTORC1 are thought to play a key role in neuronal and synaptic plasticity and dentritic morphogenesis through regulation of protein synthesis (Kumar et al, 2005;Tavazoie et al, 2005;Swiech et al, 2008;Costa-Mattioli et al, 2009). mTORC1-mediated translation is required both at the synapse, for synaptic plasticity, and within the cell soma, for maintaining memory (Swiech et al, 2008;Gkogkas et al, 2010).…”
Section: Rheb In Synapse Size and Functionmentioning
confidence: 99%